AN ASSESSMENT OF SOFTWARE EFFORT ESTIMATION USING DATA MINING APPROACHES - Bhavendra Kumar Sinha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper summarizes the some of the most important developments in neural network research. Our purpose is to provide a synthesis of the published research in this area and stimulate further research interests and efforts in the identified topics. This model carries some the desirable features of COCOMO by using the various approaches, while maintaining the merits of COCOMO model. The models deal effectively with imprecise and uncertain input and enhance the reliability of software cost estimation. Our proposed methodology is based on standard COCOMO model; FSS algorithmic based K-Mean clustering and an ANN or SVM model. We briefly review these techniques in this paper.